Layer-by-layer growth in solution deposition of monocrystalline lead sulfide thin films on GaAs(111). (3rd June 2019) - Templeman, Tzvi; Perez, Maayan; Friedman, Ofir; Abutbul, Ran Eitan; Shandalov, Michael; Ezersky, Vladimir; Konovalov, Oleg; Golan, Yuval
Abstract : In situ synchrotron GIXD showed layer-by-layer growth in solution deposited monocrystalline thin films of lead sulfide on GaAs(111). Abstract : We report layer-by-layer growth of single crystal PbS films with unprecedented quality using chemical solution deposition, on par with much more sophisticated growth techniques. Ex situ transmission electron microscopy and in-house X-ray diffraction established the monocrystalline nature of the films and the atomically smooth film surface. High brilliance synchrotron X-rays were employed in grazing incidence geometry for in situ monitoring the formation of a gallium sulfide interfacial layer, and for establishing layer-by-layer growth of the subsequent PbS film. Our findings show that by maintaining a large reservoir of free sulfide ions, layer-by-layer growth is maintained by reducing the interfacial surface free energy.